2019
DOI: 10.1021/acs.inorgchem.9b00344
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Automated Refinement (SCAR): A Data-Driven Method for Determining Inorganic Structures

Abstract: Single-crystal diffraction is one of the most common experimental techniques in chemistry for determining a crystal structure. However, the process of crystal structure determination and refinement is not always straightforward. Methods for simplifying and rationalizing the path to the most optimal crystal structure model have been incorporated into various data processing and crystal structure solution software, with the focus generally on aiding macromolecular or protein structure determination. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…57 Auxiliary machine-learning tools to assist in site assignments may prove helpful. 58 In addition to confirming positive predictions from the machine-learning model, testing negative predictions is important to evaluate the degree to which false negative errors arise. An equal number of "unlikely" candidates (CrGaSn, CrMoNi, CuRuNb, MoHfNi, NiAgNb, VHfAg, ZrRuNb) were identified that have low probabilities (<50%) of adopting half-Heusler structures and that contain at least one component in common with the high-probability candidates characterized above.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Auxiliary machine-learning tools to assist in site assignments may prove helpful. 58 In addition to confirming positive predictions from the machine-learning model, testing negative predictions is important to evaluate the degree to which false negative errors arise. An equal number of "unlikely" candidates (CrGaSn, CrMoNi, CuRuNb, MoHfNi, NiAgNb, VHfAg, ZrRuNb) were identified that have low probabilities (<50%) of adopting half-Heusler structures and that contain at least one component in common with the high-probability candidates characterized above.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, varying experimental conditions may lead to different types and degrees of disorder . Auxiliary machine-learning tools to assist in site assignments may prove helpful …”
Section: Resultsmentioning
confidence: 99%
“…Apart from traditional laboratory experiments and computational material simulation approaches, artificial Intelligence (AI) could be an alternative approach that is able to address the material design challenges mentioned above. For example, ML methods have already managed to (1) automate materials' characterization processes and effectively analyze the characterization dataset, [18][19][20][21] (2) quickly screen the vast material design space (e.g., reducing the prediction time of DFT from 10 3 s to 10 À2 s), [22][23][24][25] (3) realize property prediction in complex material systems with limited first-principles understanding, 26 (4) directly map high-dimensional synthesis recipes to materials with desired properties, 27,28 and (5) extract generalizable scientific principles from various material systems. 27,29,30 The reason why AI is particularly apt in material design is due to its inherently strong capabilities in handling huge amounts of data as well as high-dimensional analysis.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…Anton Oliynyk's research: The Oliynyk group studies intermetallic compounds and combines machine learning methods with experimental research. [ 490–495 ] They study the inorganic chemistry of intermetallic materials with focus on energy‐converting materials and mechanical properties such as hardness and wear resistance. [ 493 ] The materials are synthesized directly from elements by high‐temperature methods, including arc‐melting and sintering.…”
Section: Overview Of Mercury Faculty Research Effortsmentioning
confidence: 99%